Canada’s Response to the Issue of Refugee Women: The Women at Risk Program - Spencer-Nimmons, Noreen (Refuge: Canada’s Journal on Refugees, 1994)
Origins of Canada’s "Women at Risk" (AWR) refugee resettlement program.